Domestic Violence During Pregnancy and Risk of Obstetrical Complications - Djam Chefor Alain; Tchinda Allende Nidelle; Kepgang Nanseu Evrard; Keumoe Fetchouang Franck; Nguemnang Nguemnang Willy Armand; Amadou Sadrack; Kouanfack Charles (Archives of Current Research International, 2024)
Context: Intimate partner violence is a phenomenon that affects a significant number of women and has an important impact on society. This conjugal violence against women can have important consequences on their health as well as on the health of the unborn child during pregnancy. Objectives and Methods: In order to assess the risk of obstetrical complications in women who are victims of domestic violence, we conducted a descriptive cross-sectional study with an analytical component to determine the association between domestic violence and obstetrical complications on the one hand, and to determine the factors associated with domestic violence on the other. The descriptive part consisted of determining the prevalence of domestic violence and neonatal complications, and describing the different types of violence. A questionnaire was self-administered to pregnant women who came for prenatal consultations at the Dschang District Hospital. Results: Amongst 320 women approached, 300 agreed to participate in the study. The overall prevalence of spousal violence was 37.33%, and the prevalence of spousal violence during pregnancy was 13.33%; the prevalence of neonatal complications was 20.7%, premature deliveries accounted for 7.7%, miscarriages 7%, stillbirths 6.7%, while the prevalence of low birth weight babies was 1.7%. Domestic violence was significantly associated with neonatal complications (OR=4.1 p value=0.000). Regarding the types of violence, verbal and psychological violence had a frequency of (108)36%, physical violence which represented (40) 13.3%, control and financial violence represented (23) 7.7% and (30) 10% respectively; sexual violence was the least represented with (20) 6.7%. Regarding the factors associated with domestic violence, the 25-34 age group of the woman (p value 0.02, OR: 4.2), consumption of alcohol by the partner (p value 0.02, OR: 4.14) and the history of violence before pregnancy (p value 0.001, OR: 92.91) were significantly associated with domestic violence. Conclusion: Early identification of abuse in pregnant women and taking steps to prevent it may reduce the occurrence of these adverse outcomes.